A bio-inspired isolator based on characteristics of quasi-zero stiffness and bird multi-layer neck. (November 2020) - Deng, Tianchang; Wen, Guilin; Ding, Hu; Lu, Ze-Qi; Chen, Li-Qun
Highlights: A bio-inspired multi-layer quasi-zero stiffness isolation system is proposed. The approximate analytical results are verified by numerical method. Vibration characteristics and the influence of system parameters are investigated. The results show that the harmonic ultra-low frequency vibration is isolated. Abstract: With the increasing of the accuracy requirement of data record for on-orbit instruments, it becomes a greater challenge and brings more opportunities in design of observing spacecraft to isolate micro-vibrations of low frequency and ultra-low frequency. By imitating both multi-vertebra structure of bird's neck and gazing stability of head, a multi-layer quasi-zero stiffness (QZS) nonlinear isolator is investigated in this paper. The mathematical model with high-order coupled nonlinear ordinary differential equations is established. Its isolation performance is analyzed by the harmonic balance method (HBM) combining with the pseudo arc length method. In comparison to the corresponding linear structure, the proposed multi-layer QZS nonlinear isolator can break the limitation of poor isolation performance in low frequency and ultra-low frequency vibration for traditional linear passive isolation systems. Also, the analysis results show that its High-Static-Low-Dynamic-Stiffness (HSLDS) property may solve the traditional contradiction between large isolation frequency band and loading capacity for reducing soft stiffness. The multi-layer QZS combined system as integration is quite capable of cumulatively expanding the effective range of dynamic displacement which is too narrow for a single QZS system. The relevant conclusions are instructive to develop preferable isolation equipment to isolate low frequency and ultra-low frequency vibration in practical engineering.